Data for: Microwave permittivity of limestone and quicklime vs temperature - Rönnow, Daniel (University of Gävle, 2026)
Data are given for the complex relative permittivity for limestone (CaCO3) and quick lime (CaO) vs temperature in the range from room temperature to 1000C. Data are given for limestone gravel during calcination. Data values recalculated to bulk CaCO3 and CaO are also given. Permittivity data for a limestone block during calcination are given together with calculated data where values for Bulk CaCO3 and CaO were used.

Data ges för komplexa relativa permittiviteten för kalksten (CaCO3) och bränd kalk (CaO) vs temperatur i området rumstemperatur till 1000C. Data ges för permittiviteten för små stenar av kalksten under kalcineringen. Data ges också för värden omräknade till bulk CaCO3 och CaO. Data ges också för ett block av kalksten under kalcineringen tillsammans med beräknade data där värden för bulk CaCO3 och CaO använts.
Data för: Mikrovågspermittiviteten för kalksten och bränd kalk vs temperatur
Keywords: chalk; krita (kalksten); limestone; kalksten; calcination; high temperature; limestone; temperature dependence; quicklime; bränd kalk; calcination; kalcinering; microwave permittivity; mikrovågspermittivitet; Other Electrical Engineering, Electronic Engineering, Information Engineering; Annan elektroteknik och elektronik